1997
DOI: 10.1001/jama.1997.03550230066039
|View full text |Cite
|
Sign up to set email alerts
|

Spread of HIV Infection in Married Monogamous Women in India

Abstract: Infection with HIV is increasing in non-FSWs, previously thought to be at low risk in India. Since history of sexual contact with their only sex partner was the only risk factor significantly associated with HIV infection, it is likely that these women are being infected by their spouses. This underscores the need for strengthening partner-notification strategies and counseling facilities in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
143
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(148 citation statements)
references
References 10 publications
2
143
2
Order By: Relevance
“…1,2 Their role as a bridge population between high-risk persons and the general population for transmitting STI/HIV has long been recognized. [3][4][5][6][7][8] Men and women working in a truck stand as transport agents or other occupations and living in, or in close proximity of, truck stands may be at higher risk for STI/HIV because of possible sexual mixing among truck drivers, sex workers, and those persons working/living in truck stand setting. 3,9,10 Copyright © 2007, American Sexually Transmitted Diseases Association All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Their role as a bridge population between high-risk persons and the general population for transmitting STI/HIV has long been recognized. [3][4][5][6][7][8] Men and women working in a truck stand as transport agents or other occupations and living in, or in close proximity of, truck stands may be at higher risk for STI/HIV because of possible sexual mixing among truck drivers, sex workers, and those persons working/living in truck stand setting. 3,9,10 Copyright © 2007, American Sexually Transmitted Diseases Association All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Thus our findings using local laboratory workers are similar to those of other researchers in multiple international settings. Recently investigators in several Asian countries have reported that infected husbands are the main cause of HIV infection among unsuspecting wives, thereby stimulating interest in testing and partner notification programmes (Gangakhedkar et al 1997;Nagachinta et al 1997). Others have stressed the importance of HIV testing and short dose zidovudine treatment to prevent mother-to-child transmission (CDC 1998).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The validity of this model has been supported by observations that heterosexuals, many of whom have no identified risk, currently are the fastest growing population of newly HIV-infected persons, both in the United States 9,10 and in the developing world. 11 These statistics strongly recommend the continued delivery of HIV prevention messages to broad, general populations such as pregnant women, as well as to smaller groups with defined high-risk factors. 8,12 There are compelling reasons to offer HIV education in urban prenatal clinics in particular, because several factors identified in the current study suggest that their clientele are at higher risk for HIV infection than other American women of childbearing age: a large proportion have a history of a previous sexually transmissible infection, they report relatively high numbers of lifetime sexual partners, and a small but measurable proportion of subjects have traded sex for *"High Risk" was assigned if the subject reported Ն10 lifetime sexual partners and either suspected or was certain that their main partner was having sexual relations with another woman.…”
Section: Discussionmentioning
confidence: 99%